Получение наноколлоидов меченных технецием-99м для лимфосцинтиграфии - Садкин В. Л. Владимир Леонидович; Скуридин В. С. Виктор Сергеевич; Стасюк Е. С. Елена Сергеевна; Нестеров Е. А. Евгений Александрович; Варламова Н. В. Наталья Валерьевна; Рогов А. С. Александр Сергеевич (2013, 2013)
В фонде НТБ ТПУ отсутствует